Season and pandemic flu – the consequences for health, social and economical issue - Marciniak, Jerzy; Szymańska, Jolanta (Polish Journal of Public Health, 2012)
Flu (influenza) is an acute infectious disease caused by the influenza virus type A, B or C of the family Orthomyxoviridae, which spreads mainly by droplet route and infected man is the source of disease. Every year 5-15% of the world population of suffer influenza, out of which in 3-5 million people with a grave course. Influenza lasts on average from a few to several days. Its episode gives immunity for the particular subtype of the virus, but the large antigenic variability of influenza viruses types A and B carries the threat of breaking that barrier and frequent infections. Most serious consequences of seasonal influenza and especially of pandemic influenza are complications within the upper and lower respiratory tract, cardiovascular system, central nervous system and kidneys. Being infected with influenza virus A, especially the subtype A/H1N1, may lead to heavy pneumonia of a primary, secondary or mixed character and bronchitis and bronchiolitis. These states require treatment in intensive therapy departments and have a high mortality rate. In cardiovascular system influenza can lead to myocarditis, myocardial insufficiency and cardiac infarction. Influenza involving the central nervous system may be the cause of meningitis, encephalitis, strokes and many neurological and psychiatric conditions. Causal treatment of influenza is very expensive and the symptomatic one - little effective. Epidemics of influenza contribute to the losses involving health as well as social and financial losses. They can be limited by the safe and effective prevention – annual preventive vaccinations with the use of vaccines including the recommended by the WHO virus strains of influenza type A and B, with simultaneously carried out relevant activities and sanitary-hygienic procedures.